Cardiac performance in patients hospitalized with COVID‐19: a 6 month follow‐up study. (27th March 2021) - Fayol, Antoine; Livrozet, Marine; Boutouyrie, Pierre; Khettab, Hakim; Betton, Maureen; Tea, Victoria; Blanchard, Anne; Bruno, Rosa‐Maria; Hulot, Jean‐Sébastien; ,
Abstract: Aims: Myocardial injury is frequently observed in patients hospitalized with coronavirus disease 2019 (COVID‐19) pneumonia. Different cardiac abnormalities have been reported during the acute COVID‐19 phase, ranging from infra‐clinic elevations of myocardial necrosis biomarkers to acute cardiac dysfunction and myocarditis. There is limited information on late cardiac sequelae in patients who have recovered from acute COVID‐19 illness. We aimed to document the presence and quantify the extent of myocardial functional alterations in patients hospitalized 6 months earlier for COVID‐19 infection. Methods and results: We conducted a prospective echocardiographic evaluation of 48 patients (mean age 58 ± 13 years, 69% male) hospitalized 6 ± 1 month earlier for a laboratory‐confirmed and symptomatic COVID‐19. Thirty‐two (66.6%) had pre‐existing cardiovascular risks factors (systemic hypertension, diabetes, or dyslipidaemia), and three patients (6.2%) had a known prior myocardial infarction. Sixteen patients (33.3%) experienced myocardial injury during the index COVID‐19 hospitalization as identified by a rise in cardiac troponin levels. Six months later, 60.4% of patients still reported clinical symptoms including exercise dyspnoea for 56%. Echocardiographic measurements under resting conditions were not different between patients with versus without myocardial injury during the acute COVID‐19 phase. In contrast, low‐level exercise (25W for 3 min) induced a significant increase in the average E/e′ ratio (10.1 ± 4.3 vs. 7.3 ± 11.5, P  = 0.01) and the systolic pulmonary artery pressure (33.4 ± 7.8 vs. 25.6 ± 5.3 mmHg, P  = 0.02) in patients with myocardial injury during the acute COVID‐19 phase. Sensitivity analyses showed that these alterations of left ventricular diastolic markers were observed regardless of whether of cardiovascular risk factors or established cardiac diseases indicating SARS‐CoV‐2 infection as a primary cause. Conclusions: Six months after the acute COVID‐19 phase, significant cardiac diastolic abnormalities are observed in patients who experienced myocardial injury but not in patients without cardiac involvement.